Retirement and health outcomes in a meta-analytical framework - Mattia Filomena; Matteo Picchio (Global Labor Organization (GLO), 2021)
This paper presents a meta-analysis on the effects of retirement on health. We select academic papers published between 2000 and 2021 studying the impact of retirement on physical and mental health, self-assessed general health, healthcare utilization and mortality. Among 275 observations from 85 articles, 28% (13%) find positive (negative) effects of retirement on health outcomes. Almost 60% of the observations do not provide statistically significant findings. Using meta-regression analysis, we checked for the presence of publication bias after distinguishing among different journal subject areas and, once correcting for it, we find that the average effect of retirement on health outcomes is small and barely significant. We apply model averaging techniques to explore possible sources of heterogeneity and our results suggest that the different estimated effects can be explained by the differences in both health measurements and retirement schemes.
Keywords: I10; J14; J26; 330; Retirement; health; meta-analysis; meta-regression; publication bias